PERAN KEPALA SEKOLAH SEBAGAI INTRUCTIONAL LEADER DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MENDALAM - Budiman, Hendri; Pratiwi, Iif; Elfisa, Yesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of the principal as an instructional leader in improving the quality of deeper learning in schools. The study employed a descriptive qualitative approach, with data collected through interviews and document analysis. The informants included the principal as the key informant, as well as teachers and the vice principal for curriculum affairs as supporting informants. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the principal enhances the quality of deeper learning through: establishing and strengthening a deeper-learning vision and mission that emphasizes student-centered learning and the development of critical, creative, collaborative, and reflective thinking; aligning instructional programs to ensure coherence among learning objectives, learning activities, and assessment so as to promote conceptual understanding and the application of knowledge; implementing improvement-oriented academic supervision followed by specific feedback on instructional processes; supporting teachers’ professional development and a culture of collaboration through professional learning forums and instructional reflection; and using learning data as a basis for improvement and follow-up actions. These findings suggest that deeper learning is more effectively developed when positioned as a school-wide quality agenda supported by consistent instructional leadership.